A Comprehensive Review of Kangguru International Education Service (KIES) Course: An Evaluation of Its English Language Program - Basith, Rayhan Izzati; Tathahira, Tathahira (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
As a consequence of globalisation, there is a growing desire for people to be able to communicate effectively in English, which has led to the expansion of private English language learning institutions. This study provides an analysis and evaluation of Kangguru International Education Service (KIES), a private English language course/school located in Aceh province. This study utilises an interview with the institution's manager to conduct a SWOT analysis on KIES, which examines the company's strengths, vulnerabilities, opportunities, and threats. KIES offers a variety of English language learning programmes and maintains international ties with other institutions to ensure the institution's continued growth and success. The research demonstrates KIES's capacity to contribute to the expansion of English language proficiency in Aceh province and reveals the significance of private English learning institutions.